2006
DOI: 10.1021/jf060461p
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Cholesterol Oxidation Products in Marinated Foods during Heating

Abstract: The objectives of this study were to develop a gas chromatography-mass spectrometry (GC-MS) method to analyze the contents of cholesterol oxidation products (COPs) in marinated eggs, pork, and juice and to compare the effect of heating time and soy sauce or sugar on the formation of COPs. By using a silica cartridge for purification and GC-MS with selected ion monitoring for detection, seven COPs, including 7alpha-hydroxycholesterol, 7beta-hydroxycholesterol, 5,6alpha-epoxycholesterol, 5,6beta-epoxycholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 17 publications
6
55
1
Order By: Relevance
“…Dominancy of β-epimer in both 7-hydroxy and epoxy derivatives was observed, which may be due to steric hindrance of the hydroxyl group at position 3 (Lee et al, 2006); other authors have also observed this trend (Lampi, Juntunen, Toivo, & Piironen, 2002;Yen et al, 2010). Both epoxy compounds can give CT under acidic conditions (Lee et al, 2006).…”
Section: Cops and Peroxides Formationmentioning
confidence: 81%
See 2 more Smart Citations
“…Dominancy of β-epimer in both 7-hydroxy and epoxy derivatives was observed, which may be due to steric hindrance of the hydroxyl group at position 3 (Lee et al, 2006); other authors have also observed this trend (Lampi, Juntunen, Toivo, & Piironen, 2002;Yen et al, 2010). Both epoxy compounds can give CT under acidic conditions (Lee et al, 2006).…”
Section: Cops and Peroxides Formationmentioning
confidence: 81%
“…This might be attributed to the conversion from 7-hydroxy derivatives into such COP (Lee, Chien, & Chen, 2006;Chen, Chien, Inbaraj, & Chen, 2012).…”
Section: Cops and Peroxides Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The SIM mode was used to detect COP. The elution order of COP was as follows: 26.5-26.9 min m/z 353, 366 for 19-OH, 27.2-27.6 min m/z 456 7b-OH, 27.8-28.1 min m/z 474 for 5a,6a-EP, and 5b,6b-EP, 29.0-29.3 min m/z 403 for triol, 30.0-30.5 min m/z 131 for 25-OH and 472 for 7-ketocholesterol [13]. Other molecular ions used to determinate particular COP are presented in Table 1.…”
Section: Gc-ms Analysis Of Copmentioning
confidence: 99%
“…These proportions should be constant; otherwise, selective losses of these lipids, into upper phase, may occur (Christie, 1993;Guardiola et al 2002). Nevertheless, it seems that this critical aspect is often overlooked in some studies (Chen, Lu, Chien, & Chen, 2010;Lee, Chien, & Chen 2006;Lee, Chien, & Chen 2008).…”
Section: Lipid Extractionmentioning
confidence: 99%